The Caring Attitude of Inpatient Nurse at Aura Syifa Hospital - Putri Kristyaningsih; Rusmawati, Aprin (Universitas STRADA Indonesia, 2023)
Background: Caring nurses are a caring attitude that makes it easier for patients to achieve improved health and recovery. Among the positive attitudes of nurses is the caring attitude of nurses. Nurses in carrying out nursing care are required to provide the best performance so that patients will feel satisfied. On the other hand, dissatisfaction will arise if the performance of the health services they receive does not match their expectations. Purpose: This study aims to determine the caring attitude of inpatient nurses at Aura Syifa Hospital, Kediri. Methods: This research is an analytical descriptive research. Data collection was carried out using a questionnaire. The patient's caring attitude assessment is carried out. Respondents were 62 patients in inpatient rooms who were selected using total sampling techniques. Data analysis was carried out by univariate statistical tests. Results: The results of research on nurses' caring attitudes were mostly positive caring attitudes, namely 58 people (93.5%), and 4 people (6.5%) who had negative caring attitudes. Conclusion: Nurses in the inpatient room at Aura Syifa Kediri Hospital have a positive caring attitude. Suggestion: This research can be used as input to improve the caring attitude of nurses towards patients in every nursing service provided to achieve patient satisfaction.